2022
DOI: 10.1002/jcp.30835
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of AZD1208 on mouse oocytes and its possible mechanisms

Abstract: AZD1208, a pan-inhibitor that can effectively inhibit PIM kinase, is used for the treatment of advanced solid tumors and malignant lymphomas. Numerous studies have proved its curative effects while its potential cellular toxicity on reproduction was still little known. In this study, we investigated the toxic effects of AZD1208 on mouse oocytes. The results showed that AZD1208 treatment did not affect meiotic resumption, but postponed oocyte maturation as indicated by delayed first polar body extrusion. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Similarly, a study using clinostat-simulated microgravity demonstrated that OPCs showed decreased proliferation and increased differentiation into astrocytes. The study also found changes in the expression of genes involved in the process of myelination [47,48].…”
Section: Opcs and Microgravitymentioning
confidence: 67%
“…Similarly, a study using clinostat-simulated microgravity demonstrated that OPCs showed decreased proliferation and increased differentiation into astrocytes. The study also found changes in the expression of genes involved in the process of myelination [47,48].…”
Section: Opcs and Microgravitymentioning
confidence: 67%
“…Previous studies using AZD1208 in vitro applied highly varying, but mostly micromolar, concentrations. Concentration-dependent effects in cell cultures have been examined with 10–40 µM (Park et al 2018 ; Yan et al 2022 ), 1–10 µM (Kreuz et al 2015 ; Harada et al 2015 ), but also from 1 nM to 3 µM (Trigg et al 2019 ). Experiments using single concentrations, again in cell cultures, often used concentrations from 1 to 5 µM (Kreuz et al 2015 ; Harada et al 2015 ; Cen et al 2014 ; Scarpa et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%